2016
DOI: 10.2147/oajsm.s109124
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory- and field-based testing as predictors of skating performance in competitive-level female ice hockey

Abstract: ObjectivesThe purpose of this study was to examine whether field-based and/or laboratory-based assessments are valid tools for predicting key performance characteristics of skating in competitive-level female hockey players.DesignCross-sectional study.MethodsTwenty-three female ice hockey players aged 15–25 years (body mass: 66.1±6.3 kg; height: 169.5±5.5 cm), with 10.6±3.2 years playing experience volunteered to participate in the study. The field-based assessments included 20 m sprint, squat jump, countermov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
1
11
0
1
Order By: Relevance
“…On-ice agility and lateral plyometrics were the two strongest indicators of performance relationships dependent on competition level. The two physical abilities both place an emphasis on singleleg power, which has been hypothesised to be highly relevant for ice hockey performance (9). Nonetheless, the results revealed that lateral plyometrics indicated a negative performance-related relationship dependent on competition level.…”
Section: Performance Relationships Dependent On Competition Levelmentioning
confidence: 84%
See 1 more Smart Citation
“…On-ice agility and lateral plyometrics were the two strongest indicators of performance relationships dependent on competition level. The two physical abilities both place an emphasis on singleleg power, which has been hypothesised to be highly relevant for ice hockey performance (9). Nonetheless, the results revealed that lateral plyometrics indicated a negative performance-related relationship dependent on competition level.…”
Section: Performance Relationships Dependent On Competition Levelmentioning
confidence: 84%
“…Although the single-leg lateral jump has not been directly tested in relating studies, research indicates unilateral tests may be more appropriate for ice hockey due to skating kinematics (9). Thus, the procedure followed the test outlines as described by Lockie et al (16).…”
Section: -Single-leg Lateral Jumpmentioning
confidence: 99%
“…The best predictors of success in the recruitment process were time to peak power and relative peak power as measured by the 30s Wingate test, VO2max and 30 m sprint forwards on ice (Roczniok et al, 2015). Fieldbased assessments seem to deliver more meaningful/predictive data compared to laboratory assessments (Henriksson, Vescovi, Fjellman-Wiklund, & Gilenstam, 2016). Henriksson et al (2016) identified single-leg standing long-jump as a valid method to gain knowledge about performance characteristics for skating among female ice hockey players.…”
Section: Introductionmentioning
confidence: 98%
“…However, few studies have compared body composition estimates from DXA and SKF in female athletes (23,38) and none included women's ice hockey players. The literature on body composition in women's ice hockey players is relatively limited (8,9,11,28,29), and available data are for players of different ages at various levels of play from different countries using different assessment methods. No study to date has compared body fat estimates from DXA and SKF in this athlete population.…”
Section: Introductionmentioning
confidence: 99%